التشكيلات الأسطورية في " جدارية " محمود درويش - مغربي فاروق إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تهدف هذه الدراسة إلى إلقاء الضوء على مجموعة شعرية حديثة للشاعر الكبير محمود درويش هي " الجدارية " . وإلقاء الضوء هنا كان مسلّطا على ظاهرة فنية استعملهما الشاعر بشكل لافت للنظر ، وهي الأسطورة ، والأسطورة كما هو معروف ، " ليست حكاية آلهة وقوى خارقة ، بل بناء معين تنتظمه نماذج أصلية تضمّ في إطارها الأدب ". وتواشج هذه الرموز الأسطورية أدّى إلى ظهور أصوات عديدة تلاحمت لتؤلف نسيج هذا العمل الكبير الذي عرض من خلاله الشاعر مجموعة من الرؤى التي يمكن أن تفهم على المستويين الخاص والعام ؛ فأجواء الموت والحزن التي هيمنت على الشاعر نتيجة لمرضه ، تداخلت بشكل مباشر مع الهمّ العام الذي يعيشه الشعب الفلسطيني . والأساطير التي استعملها الشاعر في هذه المجموعة الشعرية ليست غريبة ، بالمطلق ، على القارئ العربي ، فهي تنتمي إلى أساطير بلاد الشام والرافدين، وتدخل ضمن ثقافة أهلها، أما ما ينتمي منها إلى الأساطير اليونانية والرومانية فقد عرفه القارئ العربي جرّاء دخولها إلى ثقافته عبر القصيدة العربية الحديثة التي بدأها كل من السياب والملائكة ، ومن ثم أعلام مجلة " شعر " . We try in this study to shed light on Al Jedareia, our outstanding poet’s new collection. Here, we illuminate the exceptional artistic phenomenon which is myth. It is known that “myth is not just a story about gods and supernatural powers; it is a certain structure based on authentic stereotypes which include literature within their spheres.” The interlocking of these mythological symbols led to the rise of many voices that intertwisted to spin the tissue of this masterpiece, through which our poet presents some visions, which can be understood on both levels: the general and the private one. The poet was obssesed with funereal and grievous atmosphere due to his illness. All these items intertwisted directly with troublous situation of the Palestinian people. Here, the poet invested myths, which are very familiar to the reader; especially they are in the core of the Syrian and Mesopotamian mythologies. They are an essential component of these people’s culture. And those myths, that belong to Greek and Roman myths, were introduced to the Arabic reader by other outstanding poets like Al Saiab and Al Mala3keh, hence the eminents of Sh3r magazine.